A biodegradable radiopharmaceutical packaging material and a method for its preparation

CN122898015APending Publication Date: 2026-10-13JIANGSU HUAYI TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611150523.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

一种是在容器内壁涂覆聚乙烯醇亲水层,但聚乙烯醇遇水溶胀后易从基底脱离,不仅污染药液,而且自身属于不可降解材料,违背环保要求

Benefits of technology

[0022](1)本发明提供了一种可生物降解的放射性药物包装材料及其制备方法,通过在基底中引入甲基丙烯酸缩水甘油酯接枝的明胶,为涂层提供活性双键锚定位点,涂层中的甲基丙烯酰氧乙基磷酸胆碱链段在紫外光照射下与这些双键发生自由基接枝共聚,能够形成稳定的碳碳共价键,使涂层牢固结合于基底内表面,进而在水性药液环境中不会因溶胀而发生脱离。对比物理涂覆的聚乙烯醇涂层,后者遇水溶胀脱落并污染药液,本发明能够避免涂层剥离风险,保证涂层在整个药物储存周期内的结构完整性,从而持久发挥抗吸附功能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898015A_ABST
    Figure CN122898015A_ABST
Patent Text Reader

Abstract

The application discloses a biodegradable radioactive drug packaging material and a preparation method thereof, and relates to the field of radioactive drug packaging materials.The preparation method comprises the following steps: preparing a functional base film with a chemical anchoring site; preparing a biomimetic zwitterionic coating solution; coating the coating solution on the inner surface of the base film; and initiating free radical graft copolymerization under ultraviolet light irradiation in an inert atmosphere, so that the coating is anchored on the base surface through a covalent bond, and the finished product is obtained through post-curing and extraction purification.The application solves the problem of coating swelling and falling off by covalent anchoring, and forms a double physical barrier by synergizing electrostatic repulsion of a sulfonic acid group and a phosphocholine hydration film, so that non-specific adsorption of a radioactive drug can be effectively inhibited, the dynamic decoy effect of a gelatin amino group reduces drug degradation, the coating does not damage the degradation performance of the base, and therefore, the unity of the anti-adsorption function and the degradable and environment-friendly characteristics is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of radiopharmaceutical packaging materials, and more particularly to a biodegradable radiopharmaceutical packaging material and its preparation method. Background Technology

[0002] Radiopharmaceuticals play a crucial role in nuclear medicine diagnostics, with technetium-99m-labeled drugs being the most widely used due to their moderate half-life and ease of labeling. 99mTc-MIBI is the drug of choice for myocardial perfusion imaging. Its high lipid solubility, with a logarithmic oil-water partition coefficient of approximately 2.8, allows it to effectively penetrate myocardial cell membranes, but also makes it prone to adsorption onto the inner walls of packaging containers during storage. Because the physical half-life of technetium-99m is only about 6 hours, the entire process from preparation to use must be completed within a few hours; any decrease in activity concentration or degradation of chemical purity can lead to examination failure.

[0003] To reduce the environmental impact of single-use packaging, biodegradable polymer materials have gradually gained attention. Copolymers of poly(3-hydroxybutyrate) and poly(4-hydroxybutyrate) are considered candidate materials for radiopharmaceutical packaging due to their good biodegradability and processing properties. However, when storing 99mTc-MIBI, the copolymer's high crystallinity (50%-60%) and its regular hydrophobic crystalline regions cause strong van der Waals adsorption of drug molecules, resulting in an activity loss of 25%-30% within 2 hours. Furthermore, the adsorbed drug molecules undergo ligand exchange reactions under the catalysis of residual aluminum or titanium catalysts from the copolymer synthesis process, generating polar technetium ions, which significantly reduces radiochemical purity, rendering the entire batch of drug unusable.

[0004] To address the aforementioned issues, existing technologies have attempted two improvement approaches. One is to coat the inner wall of the container with a hydrophilic polyvinyl alcohol layer. However, polyvinyl alcohol swells upon contact with water and easily detaches from the substrate, not only contaminating the drug solution but also violating environmental protection requirements as it is a non-degradable material. The other approach is to directly blend zwitterionic compounds into the copolymer matrix. However, the strong polarity of zwitterions can disrupt the crystalline structure of the copolymer, leading to a significant reduction in the material's mechanical strength and failing to meet the reliability requirements of medical devices. Summary of the Invention

[0005] This invention overcomes the shortcomings of the prior art and provides a biodegradable radiopharmaceutical packaging material and its preparation method.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: Firstly, the present invention provides a method for preparing a biodegradable radiopharmaceutical packaging material, comprising the following steps:

[0007] S1. Preparation of functional basement membrane: Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) is blended with gelatin grafted with glycidyl methacrylate and plasticizer, and then melt-molded to obtain a basement membrane with chemical anchoring points.

[0008] S2. Preparation of biomimetic zwitterionic coating solution: Dissolve poly(sulfobetaine methacrylate-r-methacryloyloxyethyl phosphocholine) copolymer in a mixed solvent, add photoinitiator and crosslinking agent, and prepare coating solution;

[0009] S3. UV-induced chemical anchoring coating: The coating solution is coated on the inner surface of the base film, cured by UV irradiation under an inert atmosphere, and then subjected to post-curing treatment and extraction purification to obtain the packaging material.

[0010] In a preferred embodiment of the present invention, in step S1, the molar content of 4-hydroxybutyrate in the poly(3-hydroxybutyrate-co-4-hydroxybutyrate) is 11%-13%; the degree of grafting substitution of the glycidyl methacrylate-grafted gelatin is 55%-65%, and its addition amount is 10%-20% of the mass of the poly(3-hydroxybutyrate-co-4-hydroxybutyrate); the plasticizer is tributyl acetylacetonate, and its addition amount is 3%-7% of the mass of the poly(3-hydroxybutyrate-co-4-hydroxybutyrate).

[0011] In a preferred embodiment of the present invention, in step S1, the melt forming conditions are as follows: the blend is melt-extruded in a twin-screw extruder, with extrusion temperature zones of 140℃-150℃ in the feeding section, 155℃-165℃ in the compression section, and 150℃-160℃ in the die head, and the screw speed is 100-140 rpm; after extrusion granulation, the base film is formed by injection molding or casting, and the surface of the molding die is pre-treated with plasma, the plasma treatment atmosphere is an Ar / N2 mixture, the treatment power is 250-350 W, and the treatment time is 60-120 s.

[0012] In a preferred embodiment of the present invention, in step S2, the molar ratio of sulfobetaine methacrylate to methacryloyloxyethyl phosphocholine in the poly(sulfobetaine methacrylate-r-methacryloyloxyethyl phosphocholine) copolymer is 6.5-7.5:2.5-3.5; the number average molecular weight of the copolymer is 25,000-30,000 Da, and the dispersion coefficient is ≤1.2.

[0013] In a preferred embodiment of the present invention, in step S2, the mixed solvent is a mixture of ethanol and water, with a volume ratio of ethanol to water of 50-60:40-50; the concentration of the copolymer in the coating solution is 5.5-7.5 wt%; the photoinitiator is Irgacure 2959, and its addition amount is 0.5%-1.0% of the copolymer mass; the crosslinking agent is trimethylolpropane triacrylate, and its addition amount is 0.3%-0.8% of the copolymer mass.

[0014] In a preferred embodiment of the present invention, in step S3, the coating method is dip coating or spin coating, and the wet film thickness after coating is 70-90 μm; the wavelength of the ultraviolet irradiation is 365 nm, and the light intensity is 10-20 mW / cm². 2 The irradiation time is 5-10 minutes, and the irradiation is carried out in an inert atmosphere, which is a nitrogen or argon atmosphere.

[0015] In a preferred embodiment of the present invention, in step S3, the post-curing treatment is as follows: the irradiated product is placed in a vacuum environment at 50-70 °C for 1.5-2.5 h; the extraction and purification is as follows: the inner wall is rinsed 2-4 times with sterile water for injection at 40-70 °C to remove unanchored free copolymers, and after drying, a coating with a dry film thickness of 40-50 nm is obtained.

[0016] In a second aspect, the present invention provides a biodegradable radiopharmaceutical packaging material, prepared by any one of the above-mentioned methods, comprising:

[0017] A biodegradable poly(3-hydroxybutyrate-co-4-hydroxybutyrate) substrate membrane, and a biomimetic zwitterionic copolymer coating anchored to the inner surface of the substrate membrane by covalent bonds;

[0018] The coating comprises a poly(sulfobetaine methacrylate-r-methacryloyloxyethyl phosphocholine) copolymer, which is covalently linked by free radical graft copolymerization of the methacryloyl groups on its segments with the residual double bonds of glycidyl methacrylate-grafted gelatin in the base film.

[0019] In a preferred embodiment of the present invention, the base film contains 11%-13% molar content of 4-hydroxybutyrate in poly(3-hydroxybutyrate-co-4-hydroxybutyrate), and contains 10%-20% by mass of glycidyl methacrylate grafted gelatin and 3%-7% by mass of tributyl acetylacetate; the coating contains a molar ratio of sulfobetaine methacrylate to methacryloxyethyl phosphocholine of 6.5-7.5:2.5-3.5, and a dry film thickness of 40-50 nm.

[0020] In a preferred embodiment of the present invention, the packaging material is in the shape of a vial or a film sheet, and its inner surface is coated with the biomimetic zwitterionic copolymer coating.

[0021] This invention addresses the shortcomings of the prior art and has the following beneficial effects:

[0022] (1) This invention provides a biodegradable radiopharmaceutical packaging material and its preparation method. By introducing glycidyl methacrylate-grafted gelatin into the substrate, active double bond anchoring sites are provided for the coating. The methacryloyloxyethyl phosphocholine segments in the coating undergo free radical grafting copolymerization with these double bonds under ultraviolet light irradiation, forming stable carbon-carbon covalent bonds, which firmly bind the coating to the inner surface of the substrate, thus preventing it from detaching due to swelling in aqueous drug solutions. Compared with physically coated polyvinyl alcohol coatings, which swell and detach upon contact with water, contaminating the drug solution, this invention avoids the risk of coating peeling, ensuring the structural integrity of the coating throughout the entire drug storage cycle, thereby providing a long-lasting anti-adsorption function.

[0023] (2) The coating of this invention contains two zwitterionic units: sulfobetaine and methacryloyloxyethyl phosphocholine. The sulfonic acid group carries a negative charge under the physiological pH of the drug solution, and generates an electrostatic repulsion force with the positively charged methoxyisobutylisocyanate complex, which can push drug molecules away from the interface. The phosphocholine group has a very strong water-binding ability and can form a dense hydration film on the coating surface, constituting a steric barrier. The two physical repulsions prevent drug molecules from approaching the hydrophobic crystalline region on the substrate surface, thereby effectively inhibiting non-specific adsorption. Compared with the prior art that relies solely on single hydrophilic modification, the dual barrier of this invention does not depend on the coating thickness, and the anti-adsorption efficiency is greatly improved, thereby controlling the irreversible loss of drug activity to an extremely low level.

[0024] (3) In this invention, the arginine and lysine residues exposed on the gelatin molecular chain have amino groups, which can form reversible transient hydrogen bonds with the ether oxygen groups in the drug molecule. This weak interaction is easily broken under thermal motion. When the drug molecule is pushed away from the interface by electrostatic repulsion and hydration film, the amino group briefly holds the drug molecule and then bounces it back into the solution under thermal disturbance, thereby effectively shortening the residence time of the drug molecule near the interface, reducing the probability of the drug molecule undergoing ligand exchange reaction under the catalysis of metal impurities, thereby inhibiting the generation of polar degradation products, ensuring that the radiochemical purity of the drug is stable and meets the pharmacopoeia standard, and avoiding the scrapping of the entire batch of drugs due to substandard purity.

[0025] (4) The present invention adopts a surface coating method to form an ultra-thin coating with a nanometer-thickness only on the inner wall of the substrate. It does not change the crystal structure of polyhydroxy fatty acid ester and the regular arrangement of macromolecular chains in the substrate material. Therefore, the tensile strength and impact resistance of the substrate are completely preserved, which can meet the mechanical reliability requirements of medical devices for packaging containers. At the same time, the amount of coating material is extremely low and does not contain heavy metal components. The biodegradability of the substrate material is not affected. It can still be efficiently decomposed by microorganisms in a composting environment. It can achieve both anti-drug adsorption function and degradable and environmentally friendly characteristics after use, thus providing a practical material solution for radiopharmaceutical packaging. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0027] Figure 1 This is a schematic diagram of the structure of a biodegradable radiopharmaceutical packaging material according to the present invention. Detailed Implementation

[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0030] It should be noted that the raw materials, equipment and reagents used in this invention can all be purchased from the market or obtained through existing preparation methods.

[0031] The raw materials used in the examples and comparative examples are described below: Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)], with a 4HB molar content of 12% and a melting temperature Tm = 155℃, was purchased from Shenzhen Yikeman Biotechnology. Glycidyl methacrylate-grafted gelatin (GelMA), with a degree of graft substitution DS = 60%, was prepared in-house. The gelatin raw material used was purchased from Sigma-Aldrich (derived from pigskin, Bloom value 300), and glycidyl methacrylate was purchased from Aladdin (purity ≥ 97%). Acetyl tributyl citrate (ATBC), with a purity ≥ 99.5%, was purchased from Guangdong Yuanfeng Chemical. Sulfobetaine methacrylate (SBMA), with a purity ≥ 98%, was purchased from Aladdin. Methacryloxyethyl phosphocholine (MPC), with a purity ≥ 98%, was purchased from Shandong Borun Biotechnology. Trimethylolpropane triacrylate (TMPTA), with a purity ≥ 98%, was purchased from Aladdin. Photoinitiator Irgacure 2959, purity ≥98%, purchased from BASF. Azobisisobutyronitrile (AIBN), purity ≥98%, purchased from Sigma-Aldrich, purified by recrystallization from anhydrous ethanol before use. RAFT chain transfer agent (4-cyano-4-[(dithiopyridine)thio]valerate), purity ≥97%, purchased from Aladdin. Ethanol was analytical grade, and water was deionized water; all are standard reagents, and unless otherwise specified, all are commercially available standard specifications.

[0032] Preparation of glycidyl methacrylate-grafted gelatin (GelMA):

[0033] The gelatin raw material was dried in a vacuum oven at 60℃ for 12 hours. 20.0 g of the dried gelatin was weighed and added to 200 mL of phosphate buffer (0.1 M, pH 7.4). The mixture was mechanically stirred (300 rpm) in a water bath at 50℃ until completely dissolved. 8.5 mL of glycidyl methacrylate (approximately 3.5 times the molar amount of free amino groups in the gelatin) was slowly added dropwise to the solution at a rate of 0.5 mL / min. After the addition was complete, the mixture was reacted at 50℃ in the dark for 4 hours. After the reaction, the reaction solution was transferred to a dialysis bag with a molecular weight cutoff of 3500 Da. Dialysis was performed at 40℃ for 72 hours using water as the dialysate, with the dialysate changed every 8 hours. The dialysate was freeze-dried (-50℃, 10 Pa, 48 hours) to obtain a white, spongy GelMA. The degree of graft substitution (DS) was determined to be 60% by the TNBS method.

[0034] Synthesis of poly(sulfobetaine methacrylate-r-methacryloyloxyethyl choline phosphoric acid) random copolymer [P(SBMA-r-MPC)]:

[0035] Weigh out 19.53 g of SBMA monomer and 8.85 g of MPC monomer according to the SBMA:MPC molar ratio of 7:3, and add them together to a 500 mL Schlenk flask. Weigh out 0.420 g of RAFT chain transfer agent (4-cyano-4-[(dithiopyridine)thio]valerate) and 0.049 g of initiator AIBN, dissolve them in 200 mL of anhydrous ethanol / water (volume ratio 55:45), and pour the solution into the Schlenk flask. The system was subjected to a three-cycle of liquid nitrogen freezing-vacuuming-thawing to remove oxygen. After thawing, the reaction was magnetically stirred in an oil bath at 65 °C for 24 h. After the reaction was completed, the solution in the bottle was precipitated three times in n-hexane (the volume of the precipitant was 10 times the volume of the reaction liquid). The precipitate was dried in a vacuum oven at 40℃ for 24 hours to obtain a light yellow powdery P(SBMA-r-MPC) copolymer with a number average molecular weight Mn=27800 Da and a dispersion coefficient PDI=1.16 (GPC determination, with polyethylene glycol as the standard and 0.1M NaNO3 aqueous solution as the mobile phase).

[0036] Example 1:

[0037] A method for preparing a biodegradable radiopharmaceutical packaging material includes the following steps:

[0038] S1. Preparation of functional base membrane: P(3HB-co-4HB) particles (4HB molar content 12%) were dried in a vacuum oven at 65℃ for 6h. 100 parts by weight of dried P(3HB-co-4HB), 15 parts by weight of GelMA (DS=60%), and 5 parts by weight of ATBC were added to a high-speed mixer and premixed at 800rpm for 5min. The premix was fed into a twin-screw extruder for melt blending. The extrusion temperature zones were: feed section 145℃, compression section 160℃, die head 155℃, and screw speed 120rpm. The extrudate was granulated by water cooling to obtain functionalized masterbatch.

[0039] The masterbatch was injection molded into a standard vial shape with an inner diameter of 22 mm and a height of 45 mm using a micro injection molding machine. The injection mold temperature was controlled at 70℃. Before injection molding, the surface of the mold cavity was pre-treated with plasma in an Ar / N2 mixed gas atmosphere (volume ratio 1:1), with a power of 300W and a treatment time of 90s. After demolding, a functional substrate vial was obtained, with residual methacryloyl double bonds of GelMA exposed on its inner surface as chemical anchoring points.

[0040] S2. Preparation of the biomimetic zwitterionic coating solution: The self-synthesized P(SBMA-r-MPC) copolymer (SBMA:MPC=7:3, Mn=27800, PDI=1.16) was dissolved in a mixed solvent of ethanol / water at a volume ratio of 55:45 to prepare a copolymer solution with a concentration of 6.5wt%. 0.8% (by weight of the copolymer) of the photoinitiator Irgacure 2959 and 0.5% (by weight of the copolymer) of the crosslinking agent TMPTA were added to this solution, and the mixture was magnetically stirred at room temperature in the dark for 30 minutes until completely dissolved, yielding the biomimetic zwitterionic coating solution.

[0041] S3, UV-induced chemical anchoring coating: The coating solution prepared in S2 is injected into the inner cavity of the functional substrate vial obtained in S1 through a peristaltic pump. After maintaining the overflow state for 30 seconds, the solution is poured out and then rotated and sprayed at 2000 rpm for 45 seconds to control the wet film thickness on the inner surface of the vial to 80 μm.

[0042] The coated vials were immediately transferred into a UV curing chamber and irradiated with 365nm wavelength UV light at an intensity of 15mW / cm². 2 The irradiation time was 8 minutes. High-purity nitrogen gas (99.999% purity, flow rate 5 L / min) was continuously introduced throughout the irradiation process to maintain an inert atmosphere.

[0043] After irradiation, the vials were transferred to a 60°C vacuum oven for post-curing for 2 hours. After post-curing, the inner walls of the vials were rinsed three times with sterile water for injection at 60°C, each rinse using twice the volume of the vial, to extract and remove unanchored free copolymers. The rinsed vials were then dried in a 40°C vacuum oven for 6 hours to obtain the finished packaging material, the structure of which is as follows. Figure 1 As shown, the thickness of the dry film on the inner wall in this embodiment is 45 nm.

[0044] Example 2:

[0045] This embodiment is basically the same as that of embodiment 1, except that the molar content of 4HB in P(3HB-co-4HB) in step S1 is 11%, and the remaining steps and process parameters are completely consistent with those of embodiment 1.

[0046] Example 3:

[0047] This embodiment is basically the same as that of Embodiment 1, except that the molar content of 4HB in P(3HB-co-4HB) in step S1 is 13%, and the remaining steps and process parameters are completely consistent with those of Embodiment 1.

[0048] Example 4:

[0049] This embodiment is basically the same as Embodiment 1, except that in step S1, the amount of GelMA added is 10% of the mass of P(3HB-co-4HB), and the amount of ATBC added is 3% of the mass of P(3HB-co-4HB). The remaining steps and process parameters are completely consistent with Embodiment 1.

[0050] Example 5:

[0051] This embodiment is basically the same as Embodiment 1, except that in step S1, the amount of GelMA added is 20% of the mass of P(3HB-co-4HB), and the amount of ATBC added is 7% of the mass of P(3HB-co-4HB). The remaining steps and process parameters are completely consistent with those of Embodiment 1.

[0052] Example 6:

[0053] This embodiment is basically the same as that of Example 1, except that the SBMA:MPC molar ratio of the P(SBMA-r-MPC) copolymer in step S2 is 6.5:3.5. The remaining steps and process parameters are completely consistent with those of Example 1.

[0054] Example 7:

[0055] This embodiment is basically the same as that of Example 1, except that the SBMA:MPC molar ratio of the P(SBMA-r-MPC) copolymer in step S2 is 7.5:2.5. The remaining steps and process parameters are completely consistent with those of Example 1.

[0056] Comparative Example 1:

[0057] This comparative example uses uncoated P(3HB-co-4HB) vials (4HB molar content 12%, no GelMA and ATBC added, no plasma treatment, and no coating), and its injection molding process is the same as the mold temperature and cooling conditions in step S1 of Example 1.

[0058] Comparative Example 2:

[0059] The difference between this comparative example and Example 1 is that GelMA is not added in step S1, while the rest of the steps are exactly the same as in Example 1.

[0060] The specific steps are as follows: P(3HB-co-4HB) particles (4HB molar content 12%) were dried in a vacuum oven at 65℃ for 6 hours. 100 parts by weight of the dried P(3HB-co-4HB) and 5 parts by weight of ATBC were added to a high-speed mixer and premixed at 800 rpm for 5 minutes. The premix was then fed into a twin-screw extruder for melt blending. The extrusion temperature zones were: feed section 145℃, compression section 160℃, die head 155℃, and screw speed 120 rpm. The extrudate was water-cooled, stretched, and granulated, then injection molded into vials. The plasma treatment conditions for the mold surface were the same as in Example 1. The subsequent preparation of the S2 coating solution and the S3 coating and curing process were exactly the same as in Example 1.

[0061] Comparative Example 3:

[0062] The difference between this comparative example and Example 1 is that the UV irradiation curing step S3 is not performed.

[0063] The specific steps are as follows: A functional substrate vial is prepared according to step S1 of Example 1. A coating solution is prepared according to step S2 of Example 1. The coating solution is injected into the inner cavity of the vial and spin-coated (2000 rpm, 45 s) to form an 80 μm wet film. No ultraviolet irradiation or post-curing treatment is performed. The vial is directly air-dried at room temperature for 24 h. Then, the inner wall is rinsed three times with sterile water for injection at 60 °C and vacuum dried at 40 °C for 6 h.

[0064] Comparative Example 4:

[0065] This comparative example uses a PVA hydrophilic coating from the prior art as a control.

[0066] The specific steps are as follows: Take the same P(3HB-co-4HB) vials as Comparative Example 1 (4HB molar content 12%, no GelMA added), dissolve polyvinyl alcohol (PVA, degree of alcoholysis 98%, degree of polymerization 1700, purchased from Aladdin) in water to prepare a 5wt% aqueous solution, and heat and stir in a 95℃ water bath until completely dissolved. PVA solution is poured into the inner cavity of the vial, kept overflowing for 30 seconds, then poured out, and then spun at 2000 rpm for 45 seconds. The vials are then placed in a 60℃ vacuum oven and dried for 6 hours to obtain PVA physically coated vials.

[0067] Comparative Example 5:

[0068] The difference between this comparative example and Example 1 is that the SBMA:MPC molar ratio of the P(SBMA-r-MPC) copolymer in step S2 is 5:5, while the rest of the steps are exactly the same as in Example 1.

[0069] Comparative Example 6:

[0070] The difference between this comparative example and Example 1 is that the SBMA:MPC molar ratio of the P(SBMA-r-MPC) copolymer in step S2 is 9:1, while the rest of the steps are exactly the same as in Example 1.

[0071] Comparative Example 7:

[0072] The difference between this comparative example and Example 1 is that in step S2, a single homopolymer polysulfobetaine methacrylate (PSBMA) is used instead of the P(SBMA-r-MPC) copolymer; the remaining steps are exactly the same as in Example 1.

[0073] The preparation method of PSBMA homopolymer is as follows: referring to the RAFT polymerization method of P(SBMA-r-MPC) in the self-made material of this invention, the only difference is that only 28.38g of SBMA is used as monomer and MPC is not added. The other RAFT chain transfer agent dosage, AIBN dosage, solvent type and dosage, polymerization temperature, polymerization time and post-treatment method are the same as the synthesis method of P(SBMA-r-MPC). The number average molecular weight of the obtained PSBMA homopolymer is Mn=26500 Da and PDI=1.18.

[0074] Comparative Example 8:

[0075] The difference between this comparative example and Example 1 is that in step S2, a single homopolymer polymethacryloyloxyethyl phosphocholine (PMPC) is used instead of the P(SBMA-r-MPC) copolymer; the remaining steps are exactly the same as in Example 1.

[0076] The preparation method of PMPC homopolymer is as follows: referring to the RAFT polymerization method of P(SBMA-r-MPC) in the self-made material of this invention, the only difference is that only 28.84g of MPC is used as monomer and SBMA is not added. The other RAFT chain transfer agent dosage, AIBN dosage, solvent type and dosage, polymerization temperature, polymerization time and post-treatment method are the same as the synthesis method of P(SBMA-r-MPC). The number average molecular weight of the obtained PMPC homopolymer is Mn=28200 Da and PDI=1.15.

[0077] Comparative Example 9:

[0078] The difference between this comparative example and Example 1 is that the dry film thickness in step S3 is 80 nm (achieved by adjusting the coating solution concentration to 12 wt%), in order to verify the effect of excessive coating thickness on substrate degradation performance and coating stability. The remaining steps are exactly the same as in Example 1.

[0079] Performance testing: The performance testing methods for the packaging materials obtained in Examples 1-7 and Comparative Examples 1-9 are as follows:

[0080] Activity residual adsorption loss rate determination: Take the vials obtained from each example and comparative example, inject 99mTc-MIBI injection solution (activity concentration of 10mCi / mL, volume of 60% of the vial volume) into each vial, seal them, and place them in a 37℃ constant temperature incubator for 2 hours of contact. After contact, remove all the drug solution from the vial, and use a gamma counter to measure the total activity A0 of the drug solution before transfer and the activity A1 of the drug solution after transfer. Calculate the activity residual adsorption loss rate L according to the following formula: L=(A0-A1) / A0×100%. Five vials of each sample were measured in parallel, and the results were taken as the average value ± standard deviation.

[0081] Radiochemical purity (RCP) determination: The radiochemical purity of 99mTc-MIBI in the drug solution after 2 hours of exposure was determined by thin-layer chromatography. The stationary phase was a silica gel plate (Merck, silica gel 60 F254), and the developing solvent was acetone / dichloromethane (volume ratio 1:9). The plate was developed to a depth of 10 cm. After development, the plate was scanned using a radiometric thin-layer scanner, and the percentage of the 99mTc-MIBI main peak area to the total radioactive area (RCP value) was calculated. Each sample was measured in triplicate, and the average value was taken.

[0082] Determination of the amount of lipophilic impurity 99mTcO4-: Using the same conditions as the thin-layer chromatography method described above, the amount of polar impurity generated was calculated based on the percentage of the radioactive area of ​​the 99mTcO4- (Rf≈0.8-0.9) peak in the RCP chromatogram relative to the total area.

[0083] Biodegradability determination: Referring to GB / T 19277.1-2025 "Determination of the final aerobic biodegradability of materials under controlled composting conditions – Method for determining carbon dioxide release – Part 1: General Method", the packaging materials obtained in each example and comparative example were cut into 1cm × 1cm sheets with a thickness of 0.25mm. These sheets were mixed with a standardized composting substrate (mature compost and inert material mixed at a mass ratio of 2:1, with a total dry solids content of 50%) and placed in a biodegradation reactor. Composting was carried out for 45 days under constant temperature conditions of 58℃ ± 2℃ and an aeration rate of 50mL / min·g dry solids. The degradation rate was calculated as the ratio of the cumulative CO2 released from the material in each container to the theoretical CO2 release of the material. Three parallel reactors were set up for each sample, and the average value was taken.

[0084] Coating peeling rate determination: Vials obtained from each example and comparative example were filled with physiological saline (0.9% NaCl injection, 80% of the vial volume), sealed, and placed in a 37℃ constant temperature shaker for 24 hours (oscillation frequency 100 rpm). X-ray photoelectron spectroscopy surface elemental analysis was performed on the inner wall of the vial before and after soaking. The coating peeling rate was calculated based on the change in the atomic percentage of nitrogen: Peeling rate = (CN0 - CN1) / CN0 × 100%. Where CN0 is the atomic percentage of nitrogen on the inner wall surface before soaking, and CN1 is the atomic percentage of nitrogen on the inner wall surface after soaking. Measurements were taken at three different locations for each sample, and the average value was used.

[0085] The results of the above performance tests are shown in Table 1.

[0086] Table 1:

[0087] project Activity residual adsorption loss rate / % RCP / % 99mTcO4- formation amount / % Biodegradation rate (45d) / % Coating peeling rate (24h) / % Example 1 1.2±0.3 99.2 ≤0.5 90.5 0.3 Example 2 1.8±0.4 98.7 0.8 89.8 0.4 Example 3 1.5±0.3 98.9 0.7 91.2 0.3 Example 4 2.3±0.5 98.0 1.2 91.8 0.5 Example 5 1.4±0.3 99.0 0.6 89.2 0.3 Example 6 1.7±0.4 98.5 0.9 90.3 0.4 Example 7 1.5±0.3 98.8 0.8 90.7 0.3 Comparative Example 1 27.6±2.3 86.4 8.5 92.0 — Comparative Example 2 18.4±1.9 89.2 5.6 89.5 28.7 Comparative Example 3 22.1±2.0 87.5 6.8 90.3 41.2 Comparative Example 4 15.3±1.6 91.5 3.8 45.3 36.5 Comparative Example 5 8.6±1.1 94.2 2.9 90.1 0.8 Comparative Example 6 10.2±1.3 93.6 3.2 89.8 0.7 Comparative Example 7 7.8±1.0 95.1 2.1 90.0 0.4 Comparative Example 8 6.9±0.9 95.8 1.8 89.6 0.4 Comparative Example 9 1.8±0.4 98.5 1.0 72.4 0.5

[0088] As shown in Table 1, the activity residual adsorption loss rate of Example 1 was only 1.2% ± 0.3%, significantly lower than the 27.6% ± 2.3% of the untreated PHA bottle in Comparative Example 1, representing a reduction of 95.7%. This demonstrates that the present invention, through the synergistic mechanism of substrate anchoring and biomimetic zwitterion grafting, can effectively inhibit the hydrophobic association adsorption of 99mTc-MIBI by the PHA crystalline region. Specifically, the sulfonic acid groups of the SBMA unit carry a negative charge under the pH conditions of the drug solution, generating electrostatic repulsion between them and the positively charged MIBI complex, pushing the drug molecules away from the interface. Simultaneously, the MPC unit forms a robust hydration film on the coating surface, constituting a short-range steric barrier. This dual physical repulsion prevents drug molecules from approaching the hydrophobic crystalline region on the substrate surface.

[0089] Comparing Examples 1-3, it can be seen that when the 4HB molar content varies within the range of 11%-13%, the residual adsorption loss rate remains below 2.0%, indicating that this content range can provide sufficient anchoring points while ensuring the processing performance of the base film. Table 1 shows that the loss rate of Comparative Example 1 is 27.6%, while the loss rates of Examples 2 and 3 are 1.8% and 1.5%, respectively, demonstrating significantly better performance than the untreated PHA bottle.

[0090] Comparing Example 1 and Comparative Example 2, it can be seen that the loss rate of Comparative Example 2 is 18.4%. The results show that without the chemical anchoring points provided by GelMA, the MPC segments in the coating cannot form CC covalent bonds with the substrate. Physical entanglement alone is not enough to withstand long-term immersion in aqueous solutions. After the coating is partially peeled off, the hydrophobic region of the substrate is exposed, resulting in a large number of MIBI molecules being re-adsorbed. This verifies the irreplaceable role of the covalent anchoring mechanism in maintaining the durability of anti-adsorption.

[0091] The loss rate of Comparative Example 3 was 22.1%, which was significantly higher than that of Example 1. Due to the lack of UV-induced free radical graft copolymerization, covalent bonds could not be formed between the coating and the substrate. The coating was largely removed during the subsequent rinsing process, and the hydrophobic crystalline region of the substrate PHA was directly exposed to the drug solution, causing MIBI molecules to be captured by strong van der Waals forces, resulting in irreversible loss of activity. This confirmed the necessity of the UV-induced chemical anchoring step.

[0092] The loss rate of Comparative Example 4 was 15.3%, which was better than that of the untreated PHA bottle (Comparative Example 1), but still far worse than that of Example 1. The mechanism is that PVA only adheres to the substrate surface through physical adsorption, and the coating detaches after swelling in water and is non-degradable. In addition, the PVA coating does not have the long-range electrostatic repulsion function of SBMA, nor does it have the strong hydration layer steric hindrance effect of MPC, and cannot form a dual physical barrier. Its adsorption inhibition effect is significantly worse than that of the zwitterionic coating system of the present invention.

[0093] As shown in Table 1, the RCP of Example 1 reached 99.2%, and the amount of 99mTcO4- generated was ≤0.5%, which was significantly better than the RCP of Comparative Example 1 (86.4%) and the amount of impurities generated (8.5%). This indicates that the present invention plays a dynamic decoy role by forming reversible transient hydrogen bonds between the amino groups of arginine / lysine residues in GelMA and the ether oxygen groups of MIBI molecules. This effectively shortens the residence time of MIBI molecules near the interface, thereby reducing the probability of ligand exchange reactions to generate 99mTcO4- under the catalysis of trace metal impurities.

[0094] The RCP values ​​of Examples 4 and 5 were 98.0% and 99.0%, respectively, and the 99mTcO4- formation amounts were 1.2% and 0.6%, respectively, both meeting the pharmacopoeia requirement of ≥90%. However, the impurity formation amount in Example 4 was slightly higher than that in Examples 1 and 5. This is because when the GelMA content was 10%, the number of amino groups exposed on the substrate surface was relatively reduced, resulting in a decrease in the efficiency of the dynamic decoy in capturing MIBI and ejecting it from the interface. Consequently, the residence time of some MIBI molecules near the interface was prolonged, and the probability of catalytic degradation by metal impurities increased accordingly. When the GelMA content was 15% and 20%, the amino group density was sufficient, which could fully utilize the kinetic accelerated diffusion effect of transient hydrogen bonds, effectively controlling the impurity formation amount at a low level.

[0095] The RCP values ​​of Examples 6 and 7 were 98.5% and 98.8%, respectively, and the 99mTcO4- generation amounts were 0.9% and 0.8%, respectively, both far exceeding the pharmacopoeia standards. When the SBMA ratio was slightly reduced (Example 6), the electrostatic repulsion was weakened, and the concentration gradient flattening effect of MIBI near the interface was slightly worse, resulting in a slightly higher impurity generation amount than in Example 1. When the MPC ratio was slightly reduced (Example 7), the density of the hydration film was slightly reduced, the steric barrier effect was slightly decreased, and the RCP performance was slightly inferior to that of Example 1.

[0096] Comparison of data from Comparative Example 5 and Example 6 reveals that when the SBMA ratio increased from 5:5 to 6.5:3.5, the RCP jumped from 94.2% to 98.5%, an increase of 4.3 percentage points. However, when the SBMA ratio continued to increase from 6.5:3.5 to 7.5:2.5 (Example 7), the RCP only increased by 0.3 percentage points, and the increase slowed significantly. This indicates that SBMA:MPC = 6.5:3.5 is the critical ratio for the synergistic effect of electrostatic repulsion and the hydration layer barrier to transform from quantitative to qualitative change. Below this threshold, the negative charge density of SBMA is insufficient to form an effective long-range concentration dissipation layer, and the residence probability of drug molecules near the interface increases non-linearly, leading to a rapid increase in impurity formation.

[0097] Comparison of data from Comparative Example 7 and Example 6: The RCP of PSBMA was 95.1%, significantly lower than the RCP of all MPC-containing copolymers in Example 1. The mechanism is that PSBMA relies solely on the electrostatic repulsion of sulfonic acid groups, completely lacking the hydration film effect of phosphocholine groups. Drug molecules may still approach the interface after overcoming the electrostatic repulsion barrier and be catalyzed and degraded by metal impurities. Similarly, the RCP of Comparative Example 8 was 95.8%, slightly better than PSBMA, but still significantly worse than the examples. PMPC relies solely on the steric hindrance effect of the hydration film, completely lacking the electrostatic repulsion of SBMA. Drug molecules may still diffuse through the hydration layer to the vicinity of the interface and remain there under the drive of the concentration gradient, thus undergoing degradation. The results of Comparative Examples 7 and 8 together demonstrate that a near-zero adsorption interface antifouling effect cannot be achieved by relying solely on a single physical barrier. The long-range electrostatic repulsion of SBMA and the short-range steric hindrance of the hydration film of MPC must work synergistically to form a concentration dissipation layer at the nanoscale in order to completely repel drug molecules from the interface.

[0098] As shown in Table 1, the coating peeling rate of Comparative Example 2 was 28.7%, that of Comparative Example 3 was 41.2%, and that of Comparative Example 4 was 36.5%, all significantly higher than the 0.3% peeling rate of Example 1. The mechanism of this difference is that in Example 1, the methacryloyl groups of the MPC chain segment of the coating under ultraviolet light irradiation undergo free radical graft copolymerization with the residual methacryloyl groups on the surface of the GelMA substrate, forming a stable CC covalent bond. This chemical bond has extremely high hydrolytic stability in an aqueous environment and is not corroded by water molecules. Therefore, the coating remains intact after being shaken and soaked for 24 hours. In contrast, Comparative Example 2, lacking GelMA anchor points on its substrate, only exhibited weak physical interactions such as hydrogen bonds or van der Waals forces between the coating and the PHA substrate, making it extremely easy to peel off during immersion and oscillation. Comparative Example 3, although possessing GelMA anchor points, was not initiated by ultraviolet light, preventing the double bonds from undergoing free radical graft copolymerization. Consequently, the coating also failed to form covalent bonds, resulting in a peeling rate even higher than that of Comparative Example 2. The PVA coating in Comparative Example 4 adhered to the substrate surface solely through physical adsorption, also exhibiting a peeling rate as high as 36.5%.

[0099] The coating peeling rate of Comparative Example 9 was 0.5%, comparable to that of Example 1, indicating that even with excessively thick coatings, good bonding stability is still achieved under covalent anchoring. However, the biodegradation rate of Comparative Example 9 was only 72.4%, significantly lower than the 90.5% of Example 1, indicating that there is a critical value for coating thickness. When the dry film thickness exceeds 50 nm, although the anti-adsorption performance still improves slightly, the degradation cycle of the coating itself is significantly prolonged, and excessive cross-linking may limit the erosion of the substrate material by microorganisms.

[0100] As shown in Table 1, the biodegradation rates of Examples 1-7 are basically equivalent to the 92.0% of the untreated PHA bottle in Comparative Example 1. This result proves that the present invention uses a surface coating method to form an ultra-thin coating with a nanometer-scale thickness only on the inner wall of the substrate, without changing the crystal structure and regular arrangement of the macromolecular chains of PHA in the substrate material. Therefore, the biodegradable characteristics of the substrate material are not substantially affected, and it can still be efficiently decomposed by microorganisms in a composting environment.

[0101] The biodegradation rate of the PVA coating in Comparative Example 4 was only 45.3%, far lower than the 90.5% in Example 1. PVA itself is a non-degradable polymer material, and its CC backbone degrades extremely slowly in a composting environment. Since the PVA coating is applied to the surface of the PHA substrate by physical coating and its thickness is much greater than the nanometer scale, the coating itself cannot degrade. At the same time, its dense surface physical structure blocks the penetration of microorganisms and moisture into the PHA substrate to a certain extent, resulting in a serious decrease in the overall degradation efficiency.

[0102] The biodegradation rate of Comparative Example 9 was 72.4%, significantly lower than 90.5% in Example 1 and 92.0% in the untreated PHA bottle (Comparative Example 1). The mechanism was analyzed as follows: While the coating remained firmly attached to the substrate surface via covalent bonds and did not affect the crystalline structure of PHA after the coating thickness increased from 45 nm to 80 nm, the thicker cross-linked zwitterionic coating itself had a slower degradation rate (the polysulfobetaine and polyphosphoric choline backbones have a CC structure, resulting in a longer degradation cycle than PHA under composting conditions). Furthermore, the dense coating provided a certain physical barrier to the penetration of microorganisms and moisture into the PHA substrate surface. When the coating thickness exceeded a certain critical value, this barrier effect became apparent, and the biodegradation of the PHA substrate was significantly inhibited. Simultaneously, the thicker coating exhibited higher internal stress in the coating thickness direction, which could lead to microcracks or local defects within the coating, potentially becoming selective channels for microbial erosion of the substrate. However, the experimental data indicate that this negative effect was insufficient to offset the overall barrier effect brought about by the increased thickness.

[0103] The above description is based on the preferred embodiments of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered exemplary and non-limiting in all respects. The scope of the invention is defined by the appended claims rather than the foregoing description, and all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.

[0104] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for preparing a biodegradable radiopharmaceutical packaging material, characterized in that, Includes the following steps: S1. Preparation of functional basement membrane: Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) is blended with gelatin grafted with glycidyl methacrylate and plasticizer, and then melt-molded to obtain a basement membrane with chemical anchoring points. S2. Preparation of biomimetic zwitterionic coating solution: Dissolve poly(sulfobetaine methacrylate-r-methacryloyloxyethyl phosphocholine) copolymer in a mixed solvent, add photoinitiator and crosslinking agent, and prepare coating solution; S3. UV-induced chemical anchoring coating: The coating solution is coated on the inner surface of the base film, cured by UV irradiation under an inert atmosphere, and then subjected to post-curing treatment and extraction purification to obtain the packaging material.

2. The method for preparing a biodegradable radiopharmaceutical packaging material according to claim 1, characterized in that, In step S1, the molar content of 4-hydroxybutyrate in the poly(3-hydroxybutyrate-co-4-hydroxybutyrate) is 11%-13%; the degree of grafting substitution of the glycidyl methacrylate-grafted gelatin is 55%-65%, and its addition amount is 10%-20% of the mass of the poly(3-hydroxybutyrate-co-4-hydroxybutyrate); the plasticizer is tributyl acetyl citrate, and its addition amount is 3%-7% of the mass of the poly(3-hydroxybutyrate-co-4-hydroxybutyrate).

3. The method for preparing a biodegradable radiopharmaceutical packaging material according to claim 1, characterized in that, In step S1, the melt forming conditions are as follows: the blend is melt-extruded in a twin-screw extruder, with extrusion temperature zones of 140℃-150℃ in the feeding section, 155℃-165℃ in the compression section, and 150℃-160℃ in the die head, and the screw speed is 100-140 rpm; after extrusion granulation, the base film is formed by injection molding or casting, and the surface of the molding die is pre-treated with plasma, the plasma treatment atmosphere is an Ar / N2 mixture, the treatment power is 250-350 W, and the treatment time is 60-120 s.

4. The method for preparing a biodegradable radiopharmaceutical packaging material according to claim 1, characterized in that, In step S2, the molar ratio of sulfobetaine methacrylate to γ-methacryloyloxyethyl phosphocholine in the poly(sulfobetaine methacrylate-r-methacryloyloxyethyl phosphocholine) copolymer is 6.5-7.5:2.5-3.5; the number average molecular weight of the copolymer is 25,000-30,000 Da, and the dispersion index is ≤1.

2.

5. The method for preparing a biodegradable radiopharmaceutical packaging material according to claim 1, characterized in that, In step S2, the mixed solvent is a mixture of ethanol and water, with a volume ratio of ethanol to water of 50-60:40-50; the concentration of the copolymer in the coating solution is 5.5-7.5 wt%; the photoinitiator is Irgacure2959, and its addition amount is 0.5%-1.0% of the copolymer mass; the crosslinking agent is trimethylolpropane triacrylate, and its addition amount is 0.3%-0.8% of the copolymer mass.

6. The method for preparing a biodegradable radiopharmaceutical packaging material according to claim 1, characterized in that, In step S3, the coating method is dip coating or spin coating, and the wet film thickness after coating is 70-90 μm; the wavelength of the ultraviolet irradiation is 365 nm, and the light intensity is 10-20 mW / cm². 2 The irradiation time is 5-10 minutes, and the irradiation is carried out in an inert atmosphere, which is a nitrogen or argon atmosphere.

7. The method for preparing a biodegradable radiopharmaceutical packaging material according to claim 1, characterized in that, In step S3, the post-curing treatment is as follows: the irradiated product is placed in a vacuum environment at 50-70 °C for 1.5-2.5 h; the extraction and purification is as follows: the inner wall is rinsed 2-4 times with sterile water for injection at 40-70 °C to remove unanchored free copolymers, and after drying, a coating with a dry film thickness of 40-50 nm is obtained.

8. A biodegradable radiopharmaceutical packaging material, characterized in that, Prepared by the preparation method according to any one of claims 1-7, comprising: A biodegradable poly(3-hydroxybutyrate-co-4-hydroxybutyrate) substrate membrane, and a biomimetic zwitterionic copolymer coating anchored to the inner surface of the substrate membrane by covalent bonds; The coating comprises a poly(sulfobetaine methacrylate-r-methacryloyloxyethyl phosphocholine) copolymer, which is covalently linked by free radical graft copolymerization of the methacryloyl groups on its segments with the residual double bonds of glycidyl methacrylate-grafted gelatin in the base film.

9. The biodegradable radiopharmaceutical packaging material according to claim 8, characterized in that, The base film contains 11%-13% 4-hydroxybutyrate molar content of poly(3-hydroxybutyrate-co-4-hydroxybutyrate), and 10%-20% by mass of glycidyl methacrylate grafted gelatin and 3%-7% by mass of acetylated tributyl citrate; the coating contains a molar ratio of sulfobetaine methacrylate to methacryloxyethyl phosphocholine of 6.5-7.5:2.5-3.5, and a dry film thickness of 40-50 nm.

10. A biodegradable radiopharmaceutical packaging material according to claim 8, characterized in that, The packaging material is in the shape of a vial or a film sheet, and its inner surface is coated with the biomimetic zwitterionic copolymer coating.